Analysis of the in‐plane response of earthen masonry infill panels partitioned by sliding joints. (2nd February 2016) - Preti, Marco; Bettini, Nicola; Migliorati, Laura; Bolis, Valentino; Stavridis, Andreas; Plizzari, Giovanni A.
Summary: The vulnerability of infilled frames represents a critical issue in many regions with high seismicity around the world where infills are typically made of heavy masonry as they are used for thermal control of the buildings because of their thermal inertia. In this context, the use of earthen masonry infills can give a superior performance because of their ability to regulate thermal‐hygrometric performance of the building and sustainability of its life‐cycle. This paper presents a numerical study on the seismic behaviour of infill walls made of earthen masonry and partitioned with horizontal wooden planks that allow the relative sliding of the partitions. The combination of the deformability of earthen masonry and the sliding mechanism occurring along the wooden planks gives a high ductility capacity to the in‐plane response of the infill and, at the same time, significantly reduces its stiffness and strength, as compared with traditional solid infills made of fired clay units. As a result, the detrimental interaction with the frame and the damage in the infill when subjected to in‐plane loading can be minimized. The numerical model is validated with results from an experimental study and is used to perform a parametric analysis to examine the influence of variations in the geometry and mechanical properties of the infill walls, as well as the configuration of the sliding joints. Based on the findings of this study, design guidelines for practical applications are provided, together with simple formulation for evaluating their performance. Copyright © 2016 John Wiley & Sons, Ltd.